DENYUT NADI DAN INTENSITAS DALAM KONDISI DEHIDRASI - Y. tovan juni samodra samodra (Universitas Singaperbangsa Karawang, 2021)
Exercise intensity is an indicator of people's performance to cope with the load when exercising. The higher the intensity the higher the pulse. Hydration is the level of fluid levels in the body. It is necessary to prove the relationship between these three things about performance in sports. The purpose of this study was to prove the relationship between the intensity indicated by pulse and dehydration conditions. The research method uses pre-test and post-test experiments. The student research sample consisted of 25 students, 19 male, and 6 female students. The study was carried out by conditioning dehydration to a level of 4% of 70% body weight. Dehydration conditioning by using a sun raincoat passively. The initial and final tests were carried out by measuring the 400-meter running performance. The pulse was measured after carrying out the 400-meter test. The data were analyzed using descriptive statistics, and T-test. The results showed that in the 4% dehydration condition, the pulse rate of performance was still at the aerobic level, the therapy was seen from the performance that was not as good as it should be in anaerobic performance (running 400m). based on research study, good suggestion for hydration status maintenance while doing exercises